Characteristic Form and Distance in High‐Level Hierarchical Structure of Self‐Aggregated Clouds in Radiative‐Convective Equilibrium - Tomoro Yanase; Seiya Nishizawa; Hiroaki Miura; Hirofumi Tomita (Geophysical Research Letters)
Abstract The nature of convective organization remains elusive, despite its importance in understanding the role of clouds in climate systems. This study reports a new type of large‐scale structure formed by the self‐organization of deep moist atmospheric convection in radiative‐convective equilibrium. To understand the natural behavior of convection unaffected by the computational domain, we conducted cloud‐resolving simulations by systematically increasing the horizontal domain size to approximately 25,000 km. We found that if the domain side length exceeded 5,000 km, the domain‐averaged thermodynamic fields and the horizontal characteristic length converged in quasi‐equilibrium, and the cloud aggregation area exhibited a mesh‐like pattern, analogous to the shallow convective organizations despite their different scales. Its characteristic length was estimated to be approximately 3,000–4,000 km. Further work is needed to understand how convective self‐aggregation simulated without the artificial domain constraint is related to the large‐scale organization of tropical convection in the real world.